Pengaruh Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), Manajemen Kompensasi, dan Manajemen Laba Terhadap Pengindaran Pajak - Retnoningsih, Sri; Wulan Budi Astuti; Setyo Mahanani; Maudina Alfiyah (Politeknik Ganesha Medan, 2024)
Tax avoidance is a strategy used by taxpayers to lower their tax liability without breaking the law. This research aims to test the influence of corporate social responsibility, good corporate governance, management compensation and profits management on tax avoidance. The research object used is mining industry companies listed on the Indonesia Stock Exchange for 20-2021. The research method used uses quantitative methods. The sampling technique uses purposive sampling. Based on the specified criteria, 65 companies were obtained. The research results explain that corporate social responsibility, good corporate governance and profits management has a significant effect on tax avoidance, but management compensation has no effect on tax avoidance.